Ultrasound diagnosis and therapeutic intervention in the spine - Ahmed, Adil S. (J Spine Surg, 2018)
Spine pathology afflicts people across the globe and is responsible for a large portion of physician visits and healthcare costs. Imaging such as plain radiographs, CT, MRI, and ultrasound is vital to assess structure, function, and stability of the spine and also provide guidance in therapeutic interventions. Ultrasound utilization in spine conditions is less ubiquitous, but provides benefits in low costs, portability, and dynamic imaging. This study assesses ultrasound efficacy in diagnosis and therapeutic interventions for spine pathology. A systematic review conducted via PubMed, MEDLINE, and Google Scholar identified 3,630 papers with eventual inclusion of 73 papers with an additional 21 papers supplemental papers subsequently added. Findings highlighted ultrasound utilization for different structural elements of the spine such as muscle, bone, disc, ligament, canal, and joints are presented and compared with radiographs, CT, and MRI imaging where relevant. Spinal curvature and mobility are similarly presented. Ultrasound efficacy for guided therapeutics about the spine is presented and assessed against other modalities. Ultrasound is a widely used and efficacious modality to guide injections about the spine. Diagnostic utility is less well studied, but shows promise in assessing fractures, posterior ligamentous stability, and intra-operative hardware placement. The low cost, portability, and dynamic imaging ability make it an attractive modality particularly for developing health systems and resource limited environments such as combat settings and the International Space Station. Further study is recommended before broad adoption in diagnostics.